Gene Silencing Mediated by siRNA-binding Fusion Proteins Is Attenuated by Double-stranded RNA-binding Domain Structure - James C Geoghegan; Brian L Gilmore; Beverly L Davidson (Elsevier, 2012)
Delivery of small interfering RNA (siRNA) targeted to specific cell types is a significant challenge for the development of RNA interference-based therapeutics. Recently, PTD-DRBD, a double-stranded RNA binding domain (DRBD) fused to the TAT protein transduction domain (PTD), was shown to be effective at delivering siRNA in a non-cell type-specific manner. Here, we evaluated the potential of DRBD as a general protein platform for targeted small interfering RNA (siRNA) delivery. We found that a single DRBD was insufficient to stably complex siRNA when fused to targeting peptides other than PTD, which facilitated nonspecific nucleic acid binding. In contrast to PTD-DRBD, fusion proteins containing two DRBDs (2× DRBD) yielded specific and stable siRNA binding. These proteins could mediate the cellular uptake of siRNA in vitro, though compared with PTD-DRBD gene silencing was attenuated by endosomal entrapment. Our findings suggest that unlike a single DRBD, 2× DRBD inhibits siRNA escape into the cytoplasm and/or induces an internalization pathway distinct from that of PTD-DRBD. Collectively, these data indicate that while 2× DRBD retains siRNA-binding activity when fused to different cell surface-interacting peptides, the utility of 2× DRBD for cell-specific RNA interference is limited without further protein engineering to enhance the bioavailability of the delivered siRNAs.